Strain Rate Effect on Acoustic Emission Characteristics and Energy Mechanisms of Karst Limestone under Uniaxial Compression - Qingsong Wang; Jianxun Chen; Jiaqi Guo; Yanbin Luo; Yao Li; Hongyu Wang; Qin Liu (Advances in Materials Science and Engineering)
In this paper, the strain rate effect on mechanical properties, failure modes, acoustic emission (AE) characteristics, and energy mechanism of the karst limestone was analyzed based on uniaxial compression tests with different strain rates (5 × 10−6–5 × 10−4/s). The results showed that the peak strength increased linearly and peak strain increased quadratically with the logarithm value of the strain rate. Moreover, the strain rate effect on elastic modulus was not significant. Under low strain rates, the rock was damaged seriously, AE signals appeared continuously, and the cumulative number of AE signals was high. Under high strain rates, the total quantity of the macroscopic cracks decreased, but the crack length extended with better coalescence. The AE peak significantly increased under high strain rates, while the cumulative AE activity significantly reduced. The energy evolution of the karst limestone failure process had significant stage characteristics, and the strain energy ratio presented an S-shape. The maximum value of the elastic strain energy at peak stress showed a linear relationship with the logarithm value of the strain rate.